2019
DOI: 10.1080/14756366.2019.1654468
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, computational studies, tyrosinase inhibitory kinetics and antimelanogenic activity of hydroxy substituted 2-[(4-acetylphenyl)amino]-2-oxoethyl derivatives

Abstract: The over expression of melanogenic enzymes like tyrosinase caused many hyperpigmentaion disorders. The present work describes the synthesis of hydroxy substituted 2-[(4-acetylphenyl)amino]-2-oxoethyl derivatives 3a-e and 5a-e as antimelanogenic agents. The tyrosinase inhibitory activity of synthesized derivatives 3a-e and 5a-e was determined and it was found that derivative 5c possesses excellent activity with IC 50 ¼ 0.0089 mM compared to standard kojic acid (IC 50 ¼ 16.69 mM). The presence of hydroxyl groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…There were small energy discrepancies in the binding affinities predicted by docking and the IC50 values of all compounds. However similar differences were also observed in comparable docking studies [38,40,41]. The ac tive sites of mTYR and hTYRP1 enzymes are characterized by a binuclear metal center (Cu and Zn ions, respectively) coordinated by six histidine residues.…”
Section: Molecular Dockingsupporting
confidence: 74%
See 1 more Smart Citation
“…There were small energy discrepancies in the binding affinities predicted by docking and the IC50 values of all compounds. However similar differences were also observed in comparable docking studies [38,40,41]. The ac tive sites of mTYR and hTYRP1 enzymes are characterized by a binuclear metal center (Cu and Zn ions, respectively) coordinated by six histidine residues.…”
Section: Molecular Dockingsupporting
confidence: 74%
“…The interaction mode of the various pigments into the binding pockets of mTYR and hTYRP1 was also assessed by a molecular docking study. This computational technique has been successfully used to predict the binding of potential inhibitors to tyrosinase en zymes [38][39][40][41][42]. To validate the docking protocol, the crystallographic inhibitor tropolone was re-docked.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Melanin has multifaceted roles; apart from giving colour to the skin, it also acts as a skin photo-protector and convert harmful UV light into harmless heat. Despite its good side, an overproduction of melanin leads to numerous undesirable skin problems including melanoma, lentigo, and post-inflammatory hyperpigmentation frequently caused by eczema, acne, and psoriasis [49,50]. Melanin also has a questioning side.…”
Section: Enzymatic Inhibitory Effectsmentioning
confidence: 99%
“…The tyrosinase inhibitory activity of acetophenone moiety has only been rarely reported [23]. Nazir et al and Rafiq et al reported that hydroxyl-substituted benzoic/cinnamic acid analogues exhibited potent tyrosinase inhibition [24,25].…”
Section: Introductionmentioning
confidence: 99%